Good Governance and The Rule Of Law - Nik Ahmad Kamal Nik Mahmod (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Good governance is basically governing in the right and just ways. Good governance relates to goodadministration at both public and private sectors. Corporate governance is synonymous and the commonusage in the private sector. Common characteristics of good governance include transparency,accountability, participatory and rule of law. Rule of law is the focus of this paper. The principle in itselfis problematic because of multifarious interpretation Nonetheless, the consensus has been that rule of lawis essential in any government and breach of its principles may lead to arbitrariness and breach offundamental rights. The paper will expound the roles of rule of law in ensuring good governance and howabuse of power and corruption have undermined rule of law seriously and subsequently affect goodgovernance.